Repair of ordinary Portland cement concrete using alkali activated slag/fly ash: Freeze-thaw resistance and pore size evolution of adhesive interface. (20th September 2021) - Fan, Jingchong; Zhang, Bo
Highlights: The freeze–thaw resistance of adhesive interface can be enhanced by repairing with alkali activated slag/fly ash. The addition of fly ash can effectively reduce harmful pores in the adhesive interface. Excessive slag content inhibits the development of C-S-H, C-A-S-H, and N-A-S-H crystals. Abstract: Adhesive interface is the weak part of old concrete after repair, which is an important factor affecting the functionality and durability of new-to-old concrete. In order to make full use of industrial solid waste, the old concrete was repaired with the mixture of slag and fly ash (SFA) as cementitious materials in this paper considering its strong cementitious effect under the condition of alkali activator. The modification of new-to-old concrete adhesive interface was studied using different mass ratio of slag to fly ash. The cohesiveness and durability of new-to-old concrete interface were investigated systematically. Pore surface fractal dimension (PSFD) was used to further explore the mechanism of improving durability adhesive interface durability. The results indicated that the splitting tensile strength and durability of adhesive interface can be improved by adjusting the mass ratio of slag to fly ash. With 50% slag addition, the defects and harmful pores in adhesive interface were the least. The contents of C-S-H, C-A-S-H, and N-A-S-H gels in adhesive interface repaired with AASFA were increased significantly, among which the OPC-G50 was most improved. The adhesive interface was the weakest part of the repaired structure, the utilization of AASFA promoted the formation of amorphous gels, which improved the microstructure density, interfacial pore volume content, mechanical behaviors and F-T resistance significantly.